Überlegungen zur expressionistischen Prosa im Kontext des expressionistischen Epochenbegriffs - Machońko, Maria (Wydawnictwo Naukowe UAM, 1993)
The article presents the state of art in the field of studies on the expressionist prose within the context of a concept of "the expressionist epoch" which raises controversies. It is a survey of methodological attitudes which were assumed by research workers belonging to various methodological schools and various scientific generations towards the expressionist prose. The result of the discussed studies consists in the fundamental controversy between the wish to resolve to univocality which accompanies every interpretation and recognition of this which is ambiguous, insinuated in the expressionist prose. The article emphasizes the necessity of verification of the statements and generalizations applied and of enriching the criteria of analysis and evaluation of the discussed prose.